Analysis method for determining low-content carbon in aluminum or aluminum alloy

By performing acid corrosion on aluminum or aluminum alloy samples and quantitative measurement of high-frequency-infrared carbon sulfur meter, the problem of difficult determination of low-level carbon content in the prior art is solved, and high-precision and stable analysis results are achieved.

CN119394950APending Publication Date: 2025-02-07GRIKIN ADVANCED MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411695117.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

It is difficult to accurately determine the low carbon content in aluminum or aluminum alloys, especially when the carbon content is low, the accuracy and stability of the analysis results are affected.

Method used

By making aluminum or aluminum alloy into small pieces of sample, the sample is corroded with a mixture of hydrochloric acid and pure water until the surface has a metallic luster, and then quantitation is performed using a high-frequency-infrared carbon sulfur meter Determination.

Benefits of technology

This method effectively removes surface pollution of the sample, improves the analysis accuracy of low carbon content, avoids the problem of splashing around the sample and rupture of the quartz combustion tube during combustion, and ensures the stability and accuracy of the measurement results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151905670000051
    Figure BDA0005151905670000051
  • Figure BDA0005151905670000061
    Figure BDA0005151905670000061
Patent Text Reader

Abstract

The invention relates to the technical field of gas content analysis and detection, in particular to an analysis method for measuring low-content carbon in aluminum or aluminum alloy, which comprises the following steps: formulating sampling specifications of aluminum and aluminum alloy, mixing hydrochloric acid and pure water according to a certain proportion, corroding and soaking the aluminum and aluminum alloy at high temperature until the aluminum and aluminum alloy presents metallic luster, and obtaining a sample to be measured. The carbon content in the to-be-detected aluminum or aluminum alloy sample can be accurately analyzed and calculated by setting equipment and method parameters, selecting a fluxing agent and the like. According to the invention, aluminum and aluminum alloy samples are measured by adopting a high-frequency furnace slow changing mode, so that fracture of a quartz combustion tube and fluctuation of an analysis result caused by splashing of blocky samples during combustion are effectively avoided, and the effectiveness of a measurement result is ensured while the safety of equipment is protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an analytical method for determining low-content carbon in aluminum or aluminum alloy, and belongs to the technical field of gas content analysis and detection. Background Art

[0002] High-purity aluminum and its alloy materials are one of the key basic materials in the electronic information industry. They are mainly prepared by sputtering aluminum or aluminum alloy targets. In the process of sputtering to form thin films, the deposition process and performance of the targets will be affected by the purity and inclusion defects of the target materials. The carbon content in aluminum alloys has an important influence on the mechanical properties, corrosion resistance, conductivity, machinability, and electrical properties of aluminum alloys; if the carbon content is too high, it will affect the conductivity of aluminum alloys, and may also affect their electrochemical behavior. The carbon and carbides present in aluminum and aluminum alloys will cause particles during the sputtering process, thereby reducing the yield of the chip and causing coating failure. Therefore, the accurate determination of low-content carbon in aluminum or aluminum alloys is particularly important.

[0003] Part 26 of the national standard GB / T20975.26 "Chemical Analysis Methods for Aluminum and Aluminum Alloys" states: The infrared absorption method is used to determine the carbon content of 0.010%-1.00% in the chip sample, and the flux uses metal nickel chips, metal tin particles and metal tungsten particles. This method is currently the mainstream analysis method for detecting carbon content in aluminum and aluminum alloys, but it does not involve the determination method of carbon content below 0.010% in aluminum and aluminum alloy materials. Since the oxide on the surface of the aluminum block sample has not melted due to its high melting point during induction combustion, while the aluminum inside has melted, it is easy to splash around during combustion, causing the quartz combustion tube to break and the analysis results to fluctuate, which makes it difficult to accurately determine the carbon content when it is low. Summary of the invention

[0004] In view of the problems existing in the above-mentioned prior art, the present invention provides an analytical method for determining low-content carbon in aluminum or aluminum alloys, wherein the analytical method is to prepare a small sample of 0.5g-1.0g of aluminum or aluminum alloy, and to corrode the sample with a mixture of hydrochloric acid and pure water until the surface presents a metallic luster, thereby meeting the test requirements. The quantitative determination of low-content carbon in aluminum and aluminum alloys is achieved by setting the induction mode parameters of a high-frequency-infrared carbon-sulfur analyzer.

[0005] The technical solution of the present invention is as follows:

[0006] An analytical method for determining low-content carbon in aluminum or aluminum alloys comprises the following steps:

[0007] (1) Sampling aluminum or aluminum alloy, controlling the size of the aluminum or aluminum alloy sample, taking a small sample weighing 0.5g-1.0g, and the diameter of the sample does not exceed 3mm;

[0008] (2) Pre-treating the aluminum and aluminum alloy samples by using dilute hydrochloric acid as the etching solution, dissolving the aluminum or aluminum alloy sampled in the above step (1) in the etching solution, and then soaking and boiling for pre-treatment. After the surface of the aluminum or aluminum alloy presents a metallic luster, wash it with distilled water, dry it, and bottle it for later use;

[0009] (3) Turn on the high-frequency infrared carbon-sulfur analyzer, preheat for 4 hours, ventilate, set program parameters, set the induction furnace mode to slow-change mode, and set low power and high power respectively, place the aluminum or aluminum alloy sample pretreated in step (2) in a crucible, cover the sample with flux, and place it on the crucible support of the instrument;

[0010] (4) Analyze and read the results, and perform machine testing and data processing on the sample placed in the crucible holder in step (3) to obtain the carbon content in the sample.

[0011] The sample prepared by the method described in the present invention is a small block sample. Through soaking and boiling corrosion, the stability of the sample is improved to avoid the analysis error introduced by the surface material. At the same time, the power mode of the induction furnace of the equipment is set slowly to avoid the sample splashing around during combustion, causing the quartz combustion tube to break and the fluctuation of the analysis result.

[0012] Preferably, the purity of the aluminum or aluminum alloy in step (1) is ≥99.999wt%.

[0013] Preferably, the aluminum or aluminum alloy sample in step (1) is a columnar sample. This is because the aluminum or aluminum alloy is taken into a columnar sample in the present invention, and then the sample is dissolved in an acid solution for corrosion. When the aluminum or aluminum alloy is a columnar sample, its area is smaller than that of a chip-like sample, and surface contamination is easy to remove, and the reaction speed is easy to control, thereby improving the detection accuracy.

[0014] Preferably, the specifications of the columnar sample are

[0015] Preferably, the pretreatment method in step (2) is: corroding the aluminum or aluminum alloy sample with dilute hydrochloric acid, the volume ratio of hydrochloric acid to pure water is 1:10 to 2:8, and the preferred ratio is 1:9 to 1:6.

[0016] Preferably, the corrosion temperature in step (2) is 80-100° C., and the corrosion time is 5-10 min. More preferably, the corrosion temperature is 82-95° C., and the corrosion time is 6-10 min.

[0017] Preferably, the induction furnace mode in step (3) is set to a slow-change mode, the low power of the induction furnace is set at 20%-30%, and the high power is set at 70%-80%. The ventilation is nitrogen and oxygen, and the time is 30-40 minutes.

[0018] Preferably, the flux is a tungsten-tin flux, for example, a LECOⅡ type flux, and the mass of the added flux is not less than the mass of the aluminum or aluminum alloy sample.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention specifies the sample specifications and weights of aluminum and aluminum alloys, prepares an acidic etching solution, and then performs surface pretreatment on the sample to be tested, thereby effectively removing surface contamination and improving the accuracy of low-content carbon analysis.

[0021] (2) The present invention adopts the high-frequency furnace slow change mode to measure the samples of aluminum and aluminum alloys, which effectively avoids the splashing of block samples during combustion, the breakage of the quartz combustion tube and the fluctuation of the analysis results. While protecting the safety of the equipment, it also ensures the validity of the measurement results.

[0022] (3) The present invention provides an analytical method for determining low-content carbon in aluminum or aluminum alloys. The analytical method is simple and easy to operate. DETAILED DESCRIPTION

[0023] The present invention is described in detail below in conjunction with specific embodiments. The entire technical solution constituted by the following embodiments is not intended to limit the protection scope of the present application, but is merely an enumeration of an embodiment of the present invention.

[0024] Example 1

[0025] Sample purity ≥ 99.999wt% pure aluminum, the size specifications are The columnar sample has a total mass of about 0.8 grams. The pure aluminum after sample preparation is corroded for 8 minutes using dilute hydrochloric acid with a volume ratio of hydrochloric acid to pure water of 1:9, wherein the corrosion temperature is 90°C. After the surface shows metallic luster, it is washed and dried with distilled water to obtain the pretreated pure aluminum;

[0026] After the high-frequency-infrared carbon-sulfur analyzer is preheated for 4 hours and ventilated for 30 minutes, the program parameters are set, the induction furnace mode is set to the slow-change mode, and the low power and high power of the induction furnace are set respectively, where the low power is set at 25% and the high power is set at 75%. The sample is placed in the crucible, and the LECOⅡ type flux (a tungsten-tin flux) is covered on the sample. The mass of the flux added is 1 gram, and it is placed on the crucible support of the instrument;

[0027] The sample placed in the crucible holder obtained by the above operation was tested and data processed on the machine to obtain the carbon content of the sample. The test was repeated 3 times, and then the relative standard deviation RSD and the spiked recovery rate (%) were calculated. The specific results are shown in Tables 1 and 2.

[0028] The equipment model used in the on-machine testing process in this embodiment is LECO-CS844.

[0029] Example 2

[0030] Sample purity ≥ 99.999wt% pure aluminum, size specifications The columnar sample has a total mass of 0.8 g. The pure aluminum after sample preparation is corroded for 8 minutes using dilute hydrochloric acid with a volume ratio of hydrochloric acid to pure water of 1:9, wherein the corrosion temperature is 90°C. After the surface shows metallic luster, it is washed and dried with distilled water to obtain the pretreated pure aluminum;

[0031] After the high-frequency infrared carbon-sulfur analyzer is preheated for 4 hours and ventilated for 35 minutes, the program parameters are set, the induction furnace mode is set to the slow-change mode, and the low power and high power of the induction furnace are set respectively, where the low power is set at 20% and the high power is set at 70%. The sample is placed in the crucible, 0.9 grams of LECOⅡ type flux is covered on the sample, and placed on the crucible support of the instrument;

[0032] The sample placed in the crucible holder obtained by the above operation was tested and data processed on the machine to obtain the carbon content of the sample. The test was repeated 3 times, and then the relative standard deviation RSD and the spiked recovery rate (%) were calculated. The specific results are shown in Tables 1 and 2.

[0033] The equipment model used in the on-machine testing process in this embodiment is LECO-CS844.

[0034] Example 3

[0035] Sample purity ≥ 99.999wt% pure aluminum, size specifications The columnar sample has a total mass of 0.7 g. The pure aluminum after sample preparation is corroded for 8 minutes using dilute hydrochloric acid with a volume ratio of hydrochloric acid to pure water of 2:8, wherein the corrosion temperature is 90°C. After the surface shows metallic luster, it is washed and dried with distilled water to obtain the pretreated pure aluminum;

[0036] After the high-frequency infrared carbon-sulfur analyzer is preheated for 4 hours and ventilated for 40 minutes, the induction furnace mode is set to the slow-change mode, and the low power and high power of the induction furnace are set respectively, with the low power set at 30% and the high power set at 80%. The sample is placed in the crucible, 1 gram of LECOⅡ flux is covered on the sample, and placed on the crucible support of the instrument;

[0037] The sample placed in the crucible holder obtained by the above operation was tested and data processed on the machine to obtain the carbon content of the sample. The test was repeated 3 times, and then the relative standard deviation RSD and the spiked recovery rate (%) of the carbon content were calculated. The specific results are shown in Tables 1 and 2.

[0038] In this embodiment, the equipment model used in the on-machine detection process is LECO-CS844.

[0039] Example 4

[0040] The difference between this embodiment and embodiment 1 is that the etching temperature in step (1) is 100° C., and the rest is the same as embodiment 1. The results are shown in Tables 1 and 2.

[0041] Example 5

[0042] The difference between this embodiment and embodiment 1 is that the etching time in step (1) is 10 minutes, and the rest is the same as embodiment 1. The results are shown in Tables 1 and 2.

[0043] Example 6

[0044] The difference between this embodiment and embodiment 1 is that the etching time in step (1) is 5 minutes, and the rest is the same as embodiment 1. The results are shown in Tables 1 and 2.

[0045] Example 7

[0046] The difference between this embodiment and embodiment 1 is that step (1) prepares pure aluminum with a purity of ≥99.999wt% as a material with a size specification of The columnar sample was prepared by mixing the samples of the embodiment 1 and the rest was the same as that of the embodiment 1. The results are shown in Tables 1 and 2.

[0047] Comparative Example 1

[0048] The difference between this comparative example and Example 1 is that the induction furnace mode in step (2) is set to the normal mode and the induction furnace power is set to 80%, and the rest is the same as Example 1. The results are shown in Table 1.

[0049] Comparative Example 2

[0050] The difference between this comparative example and Example 1 is that the etching solution in step (1) is pure hydrochloric acid, and the rest is the same as Example 1. The results are shown in Table 1.

[0051] Comparative Example 3

[0052] The difference between this comparative example and Example 1 is that the etching solution in step (1) is pure nitric acid, and the rest is the same as Example 1. The results are shown in Table 1.

[0053] Comparative Example 4

[0054] The difference between this comparative example and Example 1 is that in step (1), aluminum or aluminum alloy with a purity of ≥99.999 wt% is prepared as a chip sample with a size of 2 mm*2 mm, and the rest is the same as Example 1. The results are shown in Table 1.

[0055] Comparative Example 5

[0056] The difference between this comparative example and Example 1 is that the etching temperature in step (1) is 50° C., and the rest is the same as Example 1. The results are shown in Table 1.

[0057] Comparative Example 6

[0058] The difference between this comparative example and Example 1 is that the etching time in step (1) is 3 minutes, and the rest is the same as Example 1. The results are shown in Table 1.

[0059] Tests and Results

[0060] Testing method of relative standard deviation RSD: In each embodiment, the carbon content of aluminum or aluminum alloy is analyzed three times to calculate the relative RSD; Spiked recovery rate: Carbon is added to the pure aluminum sample to calculate the spiked recovery rate.

[0061] The test results of the above embodiments and comparative examples are shown in Table 1.

[0062] The spike recovery results are shown in Table 2.

[0063] Table 1 Test results of embodiments and comparative examples

[0064]

[0065]

[0066] Table 2 Example spike recovery test results

[0067] / Added amount / (ug / g) Measured amount / (ug / g) Spiked recovery rate (measured amount / spiked amount*100%) Example 1 10 9.0 90 Example 2 10 9.5 95 Example 3 10 10.2 102 Example 4 10 10.0 100 Example 5 10 9.8 98 Example 6 10 9.6 96 Example 7 10 9.7 97

[0068] From the data in Table 1 and Table 2, we can see the following:

[0069] (1) The present invention provides an analytical method for determining low-content carbon in aluminum or aluminum alloy. It can be seen from the data in Tables 1 and 2 that when the test data and conditions of Examples 1 to 7 are within the scope of the present invention, the relative standard deviation RSD values ​​are all below 3, and the spiked recovery rates are all above 90%. It can be seen that the analytical method of the present invention fixes the sampling method and sample state, reduces sample surface contamination, controls the concentration of the etching solution and the etching temperature, ensures the etching efficiency and quality, ensures that the surface contamination is completely removed, changes the power of the induction furnace, and adopts a slow change in the power of the induction furnace to prevent the temperature from rising too fast, causing aluminum and aluminum alloys to dissolve first, causing violent reactions and splashing, and damaging the quartz tube; the analytical method obtains samples of appropriate size, increases the sampling amount, and reduces the sample surface area as much as possible while ensuring good solubility. Acid corrosion is used to completely remove sample surface contamination, tungsten-tin flux is used to reduce carbon pollution brought in by the flux, and the induction furnace adopts a slow change in power to prevent aluminum and aluminum alloys from reacting violently and causing splashing.

[0070] (2) Combining Example 1 and Example 4, it can be seen that the corrosion temperature of step (1) in Example 1 is 90°C, compared with the corrosion temperature of step (1) in Example 4 being 100°C, the RSDs of the test result data are 2.9 and 3.0 respectively, and the spiked recoveries are 90% and 100%. This shows that the present invention controls the corrosion temperature within a certain range, can control the corrosion time, make the corrosion thorough, improve the detection efficiency, and make the data more stable;

[0071] (3) Combining Example 1 and Examples 5-6, it can be seen that the sample corrosion time in step (1) of Example 1 is 8 minutes. Compared with the sample corrosion time in step (1) of Examples 5-6, which is 10 minutes and 5 minutes respectively, the RSD of the test result data is 2.9, 2.6 and 1.8 respectively, and the spike recovery is 90%, 98% and 96%. This shows that controlling the corrosion time can ensure the thoroughness of sample corrosion, the size of the sample after corrosion is appropriate, improve the detection efficiency, and make the data more stable;

[0072] (4) In combination with Example 1 and Example 2-3, it can be seen that in Example 1, step (2) wherein the low power is set at 25% and the high power is set at 75%, compared with Example 2, step (2) wherein the low power is set at 20% and the high power is set at 70%, compared with Example 3, step (2) wherein the low power is set at 30% and the high power is set at 80%, the RSDs of the test result data are 2.9, 2.8 and 1.9, respectively, and the spiked recoveries are 90%, 95% and 102%, which indicates that controlling the furnace heating rate and using slowly varying power can both completely dissolve the sample and prevent sample splashing, thereby improving detection efficiency and making the data more stable;

[0073] (5) Combining Example 1 and Example 7, it can be seen that in step (1) of Example 1, pure aluminum with a purity of ≥99.999wt% is prepared into a size specification of Compared with the columnar sample prepared in step (1) of Example 7, the pure aluminum with a purity of ≥99.999wt% is of size specification For the columnar samples, the RSD of the test results were 2.9 and 2.3, and the spike recoveries were 90% and 97%. This shows that controlling the sample size and state can not only facilitate the acquisition of the appropriate sample weight, but also prevent splashing caused by the sample being too large, thereby improving the detection efficiency and making the data more stable.

[0074] In contrast, in each comparative example, when each test data and condition was outside the scope of the present invention, the relative standard deviation RSD value was above 15, and the spiked recovery rate of the comparative example could not be discussed due to unstable data.

[0075] (6) Combining Example 1 and Comparative Example 1, it can be seen that in Example 1, the low power is set at 25% and the high power is set at 75%. Compared with the induction furnace mode set to the conventional mode and the induction furnace power set to 80% in step (2) of Comparative Example 1, the RSDs of the test result data are 2.9 and 30.5, respectively. This shows that controlling the slow change of furnace power is one of the main parameters of this method, which can make the sample dissolve completely, control the reaction speed, prevent sample splashing, improve detection efficiency, and make the data more stable.

[0076] (7) Combining Example 1 and Comparative Example 2, it can be seen that in Example 1, step (1) uses dilute hydrochloric acid with a volume ratio of hydrochloric acid to pure water of 1:9 as the etching solution. Compared with the test result data of comparative example 2 in which step (1) uses pure hydrochloric acid as the etching solution, the RSDs are 2.9 and 25.6 respectively, indicating that pure hydrochloric acid cannot remove sample surface contamination in a short time and is not considered;

[0077] (8) In combination with Example 1 and Comparative Example 3, it can be seen that in Example 1, step (1) uses dilute hydrochloric acid with a volume ratio of hydrochloric acid to pure water of 1:9 as the etching solution. Compared with the RSD of the test result data of step (1) using pure nitric acid as the etching solution in Comparative Example 2, they are 2.9 and 26.8 respectively, indicating that pure nitric acid cannot remove sample surface contamination in a short time and is not considered;

[0078] (9) Combining Example 1 and Comparative Example 4, it can be seen that in step (1) of Example 1, the aluminum or aluminum alloy with a purity of ≥99.999wt% is prepared into a size specification of Compared with the columnar sample prepared in step (1) of comparative example 4 with a purity of ≥99.999wt% of aluminum or aluminum alloy as a chip sample with a size of 2mm*2mm, the RSD of the test result data were 2.9 and 30.9, respectively, which shows that the chip sample has a large surface area, the surface contamination is not easy to remove, and the reaction is too violent, which is easy to splash, affecting the stability of the experimental data, and is not considered;

[0079] (10) Combining Example 1 and Comparative Example 5, it can be seen that the corrosion temperature in step (1) of Example 1 is 90°C, and the RSD of the test result data is 2.9 and 15.1 respectively, compared with the corrosion temperature in step (1) of Comparative Example 5 is 50°C. This shows that the corrosion temperature of the sample is too low, the surface contamination is not completely removed, and the stability of the experimental data is affected, so it is not considered;

[0080] (11) In combination with Example 1 and Comparative Example 6, it can be seen that in step (1) of Example 1, the pure aluminum after sample preparation is corroded for 8 minutes using dilute hydrochloric acid with a volume ratio of hydrochloric acid to pure water of 1:9. Compared with step (1) of Comparative Example 6, the pure aluminum after sample preparation is corroded for 3 minutes using dilute hydrochloric acid with a volume ratio of hydrochloric acid to pure water of 1:9, the RSDs of the test result data are 2.9 and 16.2, respectively. This shows that the sample corrosion time is too short, the surface contamination is not completely removed, and the stability of the experimental data is affected, so it is not considered;

[0081] In summary, the present invention provides an analytical method for determining low-content carbon in aluminum or aluminum alloys. The analytical method fixes the sampling method and the sample state, reduces sample surface contamination, controls the concentration of the etching solution, the etching temperature, ensures the etching efficiency and quality, ensures that the surface contamination is completely removed, changes the induction furnace power, and adopts a slow change in the induction furnace power to prevent the temperature from rising too fast, causing aluminum and aluminum alloys to dissolve first, causing violent reactions and splashing, and damaging the burned quartz tube; the analytical method obtains samples of appropriate size, increases the sampling amount, and reduces the sample surface area as much as possible while ensuring good solubility. Acid corrosion is used to completely remove sample surface contamination, tungsten-tin flux is used to reduce carbon pollution brought in by the flux, and the induction furnace adopts a slow change in power to prevent aluminum and aluminum alloys from violent reactions and splashing. Within the scope of the present invention, when determining low-content carbon in aluminum or aluminum alloys, the relative standard deviation is ≤3.0, and the spike recovery rate is between 90% and 102%.

[0082] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An analytical method for determining low-content carbon in aluminum or aluminum alloys, characterized in that: The following steps are involved: (1) Sampling aluminum or aluminum alloy, controlling the size of the aluminum or aluminum alloy sample, taking a small sample weighing 0.5g-1.0g, and the diameter of the sample does not exceed 3mm; (2) Pre-treating the aluminum and aluminum alloy samples by using dilute hydrochloric acid as the etching solution, dissolving the aluminum or aluminum alloy sampled in step (1) in the dilute hydrochloric acid etching solution, and then soaking and boiling the samples for pre-treatment until the sample surface presents a metallic luster, and then washing with distilled water, drying, and bottling for later use; (3) Turn on the high-frequency infrared carbon-sulfur analyzer, preheat for 4 hours, ventilate, and set program parameters, wherein the induction furnace mode is set to a slow-change mode, and low power and high power are set respectively. Place the sample pretreated in step (2) in a crucible, cover the sample with flux, and then place it on the crucible holder of the instrument; (4) Analyze and read the results, and perform machine testing and data processing on the sample placed in the crucible holder in step (3) to obtain the carbon content in the sample.

2. The analytical method for determining low carbon content in aluminum or aluminum alloy according to claim 1, characterized in that: In the step (1), the purity of the aluminum or aluminum alloy is ≥99.999wt%, and the aluminum or aluminum alloy sample is a columnar sample.

3. The analytical method for determining low carbon content in aluminum or aluminum alloy according to claim 1, characterized in that: The etching temperature in step (2) is 80-100° C., and the etching time is 5-10 minutes.

4. The analytical method for determining low carbon content in aluminum or aluminum alloy according to claim 1, characterized in that: The volume ratio of hydrochloric acid to pure water in the dilute hydrochloric acid etching solution in step (2) is 1:10 to 2:

8.

5. The analytical method for determining low carbon content in aluminum or aluminum alloy according to claim 1, characterized in that: The flux in step (3) uses tungsten-tin flux, and the mass of the added flux is not less than the mass of the aluminum or aluminum alloy sample.

6. The analytical method for determining low carbon content in aluminum or aluminum alloy according to claim 1, characterized in that: The test program parameters in step (3) are as follows: the low power of the induction furnace is set at 20%-30%, and the high power is set at 70%-80%.